Association between serum vitamin D deficiency and visceral fat indices in adolescents: The Ewha Birth and growth cohort study - Hyelim Lee; Hyunjin Park; Seunghee Jun; Hyeseung Jang; Young Sun Hong; Kyunghee Jung-Choi; Hye Ah Lee; Hyesook Park (PLoS ONE, 2025)
Purpose Vitamin D plays a crucial role in cardiometabolic health, but its association with visceral fat in adolescents remains unclear. This study aimed to evaluate the relationship between vitamin D levels visceral fat indices—Hypertriglyceridemic Waist Phenotype (HWP), Visceral Adiposity Index (VAI), and Lipid Accumulation Product (LAP)—which serve as practical markers for visceral fat. Methods This study analyzed 238 adolescents (aged 13–15) data from the Ewha Birth and Growth Study, a longitudinal Korean cohort. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured and categorized as deficiency (<20 ng/mL) or non-deficiency (≥20 ng/mL). Visceral fat was assessed using HWP, VAI, and LAP as surrogate markers for visceral adiposity. Logistic and linear regression analyses were performed to evaluate associations, adjusting for key covariates. Sensitivity analyses used alternative HWP definitions and vitamin D categorizations. Results Among 238 adolescents, 76.0% had vitamin D deficiency, and 7.1% had HWP. Logistic regression indicated a lower HWP risk in the non-deficiency group with a borderline level of significance ( p = 0.060). Sensitivity analyses confirmed a significantly lower HWP risk in the non-deficiency group under the lowered TG criterion and also showed that, in the three-category classification of vitamin D status, the non-deficiency group had a significantly lower HWP risk than the severe deficiency group, with a decreasing trend as vitamin D levels increased. Multiple linear regression showed inverse associations between vitamin D levels and log VAI ( β = –0.020, p = 0.008) and log LAP ( β = –0.018, p = 0.060). Conclusions The inverse relationship observed between vitamin D levels and visceral fat indices suggests a potential role in adiposity regulation and cardiometabolic health. Enhancing vitamin D status may help prevent obesity and reduce cardiometabolic risks in adolescents.